Job satisfaction and professional motivation of staff: elements, indicators and factors ("Journal "U". Economy. Management. Finance.", 2025)
The labor market is changing dynamically, and issues of job satisfaction and professional motivation of staff are becoming strategically important for ensuring the sustainable development of enterprises and organizations. Understanding how factors related to working conditions, financial and moral incentives, leadership style and socio-psychological climate affect job engagement is the key to improving work efficiency and building a competitive advantage for companies. The article analyzes the elements, indicators and factors that determine job satisfaction and professional motivation of staff. The article analyzes the interrelationships between such concepts as job involvement, wages, financial and moral incentives, staff motivation, labor productivity, professional aptitude, professional growth, leadership style, socio-psychological climate, stress, job satisfaction, personnel management, working conditions and labor efficiency.
Keywords: salary; incentive; staff motivation; professional growth; socio-psychological climate; stress; job satisfaction; personnel management; working conditions; human capital